Detección de la “polilla del álamo”, Leucoptera sinuella (Lepidoptera: Lyonetiidae), en Argentina - San Blas, Diego German (2022)
The presence of Leucoptera sinuella (Reutti) (Lepidoptera: Lyonetiidae), commonly known as the poplar moth, is cited for the first time for Argentina and, in particular, for the province of Mendoza. This economically important microlepidoptera mines poplar leaves (Populus spp.), reducing photosynthetic activity. Additionally, it can migrate to neighboring crops, for example, apple crops, pupating in its pedicle cavity. In Chile, it has caused the quarantine rejection of this fruit in countries such as the United States and Mexico. For all these reasons, monitoring the species, analyzing its establishment and taking control measures to prevent its spreading to other regions of the country, are imperative for the evaluation of this economically important species.